Challenges of Domestic Water Consumption in Bhahumono Communities of Abi Local Government Area, Nigeria - Otu, Judith E.; Eja, Eja I.; Agbor, Emmanuel A.; Inyang, Ita O. (Mediterranean Journal of Social Sciences, 2012)
The menace of domestic water consumption and quality in Bhahumono Communities, in Abi Local Government Areahas become of great concern especially among stakeholders saddle with the responsibility of maintaining quality water fordomestic and public uses. This paper examines the challenges of domestic water consumption in Bhahumono communities withspecific reference to sources of water supply, elemental contents of the difference sources, the rate of consumption and waterborne diseases in the area. Seventeen water points were sampled in selected location and the water samples collected wereanalyzed using Gallenkamp flame analyzer (model F.A. 330-9 and atomic absorption spectromometer (model PYE UNICAMSP29007. The tritrimetric and observatory methods were used to determined the physical properties of the water. The analysisshows that most sampled location had a high level of iron (fe) and cadmium (cd) which makes the not suitable for drinking asevidence in F-value of 4.62 (calculated) higher than critical value of 3.04 (calculated). A calculated value of 4.60 at 0.05significant level higher than critical value of 3.60 which indicate that distance was a major determinant factor affecting the qualityof water supply in Bhahumono communities. Therefore, adequate measures must be put in place if the menace of domesticwater quality in the area must be averted.